Treatment advantage in HBV/HIV coinfection compared to HBV monoinfection in a South African cohort. Issue 1 (July 2020) - Maponga, Tongai G.; McNaughton, Anna L.; van Schalkwyk, Marije; Hugo, Susan; Nwankwo, Chikezie; Taljaard, Jantjie; Mokaya, Jolynne; Smith, David A.; van Vuuren, Cloete; Goedhals, Dominique; Gabriel, Shiraaz; Andersson, Monique I.; et al.
Highlights: We compared HBV monoinfection with HBV/coinfection in a cross-sectional cohort from South Africa. HBV/HIV coinfected individuals were more likely to undergo assessment by fibroscan. HBV monoinfection was less likely to be treated than HBV/HIV coinfection. Indications of severe liver disease were more common in HBV monoinfection. Cases of hepatocellular carcinoma all arose in HBV monoinfection. Abstract: Objectives: Prompted by international targets for elimination of hepatitis B virus (HBV), we set out to characterise individuals with HBV monoinfection vs. those coinfected with HBV/HIV, to evaluate the impact of therapy and to guide improvements in clinical care. Methods: We report observational data from a real world cross-sectional cohort of 115 adults with chronic hepatitis B infection (CHB), at a university hospital in Cape Town, South Africa. HIV coinfection was present in 39 (34%) subjects. We recorded cross-sectional demographic, clinical and laboratory data. Results: Compared to those with HIV coinfection, HBV monoinfected adults were less likely to be HBeAg-positive (p=0.01), less likely to have had assessment with elastography (p<0.0001), and less likely to be on antiviral treatment (p<0.0001); they were more likely to have detectable HBV viraemia (p=0.04), and more likely to have features of liver disease including moderate/severe thrombocytopaenia (p=0.007), elevated bilirubin (p=0.004), and elevated APRI score (p=0.02). Three cases of hepatocellular carcinoma all arose in HBV monoinfection. Conclusions: Our data demonstrate that individuals with HBV monoinfection may be disadvantaged compared to those with HIV coinfection, highlighting potential systematic inequities in referral, monitoring and treatment.